Eksodus Ekologis: Teologi Pembebasan Asghar Ali Enginner sebagai Paradigma Pemulihan Ekologi di Indonesia - Bangkit Adi Saputra (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2025)
This research examines the ecological liberation theology of Asghar Ali Engineer as a paradigm for ecological restoration in Indonesia. Indonesia faces severe ecological crises including deforestation, agrarian conflicts, and climate change impacts that disproportionately affect marginalized communities. This library research employs Engineer's liberation theology framework to reinterpret the Exodus narrative as an ecological liberation paradigm. The study analyzes Engineer's key principles???social tawhid, liberation of the oppressed (mustadh'afin), distributive justice, and praxis-oriented theology???and applies them to Indonesia's ecological context. The research finds that the Exodus narrative, read through Engineer's lens, provides a transformative paradigm where Pharaoh represents exploitative economic systems, enslaved Israel people symbolizes exploited nature and communities, the wilderness represents ecological transition, and the Promised Land embodies a vision of ecological justice. This paradigm offers concrete implications for interfaith solidarity, agrarian reform, and community empowerment movements in Indonesia. The study contributes to contextual theology by bridging Islamic liberation theology with ecological concerns in the Indonesian context. Keywords: Asghar Ali Engineer, Liberation Theology, Exodus Narrative, Ecological Restoration, Indonesia